ANALISIS PENGELOLAAN AMENITAS DI DESA WISATA KETAPANRAME BERBASIS PLANNING: Studi Kasus pada Desa Wisata Ketapanrame, Kecamatan Trawas, Kabupaten Mojokerto - Princes Arsaredima Fahlevi; Garsione Agni Andrea (Halu Oleo University, 2025)
This study aims to analyse the planning function in the management of amenities at Ketapanrame Tourism Village, Trawas District, Mojokerto Regency. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that the planning function has been implemented in a structured and participatory manner through five key indicators: goal setting, program formulation, budgeting, activity scheduling, and development planning. Goals are set clearly and measurably in line with the village vision; programs are formulated collaboratively involving multiple stakeholders; budgeting focuses on facilities with direct benefits to visitors through a phased development strategy; activity scheduling is adaptively arranged according to tourist seasons; and development planning considers environmental sustainability and village spatial layout. Although limited funding remains a challenge, the phased development strategy and multi-stakeholder involvement serve as adaptive measures that support the sustainable management of amenities in the tourism village.